One in three adolescent schoolgirls in urban northwest Ethiopia is stunted - Samuel Mersha Birru; Aysheshim Kassahun Belew; Amare Tariku (BMC, 2018)
Abstract Background Poor nutritional status of adolescent girls has a negative effect on the next generation as undernourished adolescents enter pregnancy with poor nutrient reserve. However, there is scarcity of evidence showing the burden of stunting among adolescent girls in Ethiopia. Therefore, the objective of this study aimed to assess prevalence of stunting and associated factors among school adolescent girls in Gondar City Administration, northwest Ethiopia. Methods Cross-sectional study was conducted from March to April, 2017. A multi-stage sampling technique was used to select812 school adolescent girls. World Health Organization Anthro-plus software was used to analyze anthropometric data into Height for Age Z-score. A multivariable logistic regression analysis was employed to identify the factors associated with stunting. Adjusted Odds Ratio (AOR) with 95% confidence interval was used to show the strength of association, while a P-value< 0.05 of was used to declare the significance of association. Results The overall prevalence of stunting among adolescent girls was 33.1% (95% CI: 29.9, 36.5). Middle age of adolescence (AOR = 0.22, 95% CI: 0.15, 0.34), unsatisfactory media exposure (AOR = 1.69, 95% CI: 1.01, 2.84) and poor mother's education (AOR = 2.84, 95% CI: 1.07, 7.94) were significantly associated with stunting. Conclusions One-third of adolescent girls are stunted in Gondar City which suggests the serious public health importance of the problem. Enhancing mother's education and media exposure are critical to address the high burden of stunting.